Accuracy Comparison of Endotracheal Tube (ETT) Placement Using Chula Formula With Manubrium Sternal Joint (MSJ) Formula - Lorena, Christya; Hamzah, Hamzah; Maulydia, Maulydia (Indonesian Journal of Anesthesiology and Reanimation, 2021)
Introduction: Intubation mistakes, such as ETT malposition, will result in serious complications. Endobronchial intubation can cause pneumothorax and contralateral lung collapse (atelectasis). On the contrary, superficial ETT could increase the risk of being released easily, leading to desaturation or even cardiac arrest. A shallow ETT position could cause the compression of the vocal cord and laryngeal nerve by ETT's cuff. An optimal position can be reached if the cuff position is 1.5-2.5 cm under the vocal cord and the tip is 3-5 cm above the carina. Several methods of ETT depth measurement based on airway length data can be an alternative, especially during the COVID-19 era, where the use of a stethoscope to check ETT depth is limited. Objectives: To analyze the accuracy of ETT depth placement using Chula and MSJ formula. Methods: We conducted the prospective comparative analytic research on 50 patients who had elective surgery in GBPT operating room at Dr. Soetomo Hospital Surabaya. The research data during the intubation and FOL (Fyber Optic Laryngoscope) from each patient were height, MSJ length, initial ETT length, the distance of carina-ETT tip, the distance of cuff-vocal cord, and final ETT length. Result: In the Chula formula group, the average patients' height was 160.60cm ± 9.738 for men and 157.76 cm ± 8.604 for women. The average MSJ length was 20.28 cm. The application of the Chula formula is more accurate because ETT revision was carried out in only 8.0% of the samples, with an average revision is 0.04. On the other hand, the ETT revision with an average of 0.868 on the MSJ formula group was conducted in 84% of the samples. This research also found a linear correlation between increasing ETT depth and body height. Conclusion: Applying the Chula formula to measure the ETT depth for Indonesian (Javanese) people is more appropriate than the MSJ formula.